Criminal liability for the collective fact. Aspects of Chilean and comparative law (2017)
The article aims to provide an answer to the problem of the basis of individual criminal responsibility for the collective acts in cases of conspiracy and criminal organizations. According to the author, the answer to this problem can be found in the risk